2011
DOI: 10.1007/s11661-011-0808-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aging Parameters on the Tensile Properties and Quality Index of Al-9 Pct Si-1.8 Pct Cu-0.5 Pct Mg 354-Type Casting Alloys

Abstract: The current study was carried out with a view to investigating the influence of age-hardening parameters, aging temperature and time, on the tensile properties and quality indices of a highstrength Al-9 pct Si casting alloy, namely, 354-Al-9 pct Si-1.8 pct Cu-0.5 pct Mg. Quality charts were used as an evaluation tool for selecting the optimum conditions to be applied, in practice, in order to develop high strength and optimum quality in 354 casting alloy. Aging at a low temperature of 428 K (155°C) was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 35 publications
(57 reference statements)
3
18
0
Order By: Relevance
“…At 160 °C aging temperature, the lowest investigated temperature, a slow initial hardness increase from the as cast condition is registered as a result of the low rate of atomic diffusion related Figure 9, it is clear that the aging temperature plays an important role on precipitation hardening. Similarly to what has been observed by other studies, by increasing the aging temperature, the time required to reach the peak is reduced [24,35] and, with the exception of 160 • C, the peak hardness is generally reduced [30,36,37]. At 160 • C aging temperature, the lowest investigated temperature, a slow initial hardness increase from the as cast condition is registered as a result of the low rate of atomic diffusion related to this temperature.…”
Section: (Ii) Solution Treatment Optimization-2nd Stagesupporting
confidence: 83%
“…At 160 °C aging temperature, the lowest investigated temperature, a slow initial hardness increase from the as cast condition is registered as a result of the low rate of atomic diffusion related Figure 9, it is clear that the aging temperature plays an important role on precipitation hardening. Similarly to what has been observed by other studies, by increasing the aging temperature, the time required to reach the peak is reduced [24,35] and, with the exception of 160 • C, the peak hardness is generally reduced [30,36,37]. At 160 • C aging temperature, the lowest investigated temperature, a slow initial hardness increase from the as cast condition is registered as a result of the low rate of atomic diffusion related to this temperature.…”
Section: (Ii) Solution Treatment Optimization-2nd Stagesupporting
confidence: 83%
“…Ammar et al [6] described the microstructure of A356 alloys consisting of primary Al-1% Si dendrites and a eutectic with silicon particles (12 pct volume) embedded in the Al-1% Si matrix. Room temperature constant amplitude fatigue tests revealed that for a low crack-tip driving force, the surface fatigue crack propagated primarily through the Al-1% Si dendrite cells.…”
Section: Si Particlesmentioning
confidence: 99%
“…8(a) with Fig. 9(a) reveals that increasing the solution heat treatment time did not further improve the mechanical properties and quality index values of the alloys containing Fe and Mg but without Be and Sr [23][24][25][26][27][28] additions.…”
Section: Q-chartsmentioning
confidence: 99%